Emerging trends in Indian Sociology/edited by Ishwar Modi - "Modi, Ishwar(ed.)" (Jaipur, 1986)
These volumes constitute a compendium of the emerging trends of sociology in India. The essay in these volumes written by the distinguished sociologists and social scientists of India as well as the emerging young scholars from all over the country present a scenario of the developments and growth of the discipline of sociology in India in all its vividness, diversity and creativity reflecting the varied concerns and commitments. A new identity of Indian sociology emerges out of these volumes. This is an identity reflecting the inner search and dynamism towards building a desired type of society and the role of Sociologists and social scientists in the task of national development.
Keywords: Sociology